Kajian Infrastruktur Pengolahan Sampah di Kawasan Berkembang Jakabaring Kelurahan 15 Ulu Kota Palembang - Ikhsandri Ikhsandri (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Jakabaring is one of the growing areas in the city of Palembang. Jakabaring regional development concept itself is becoming the office central and integrated residence. Along the residence development will impact on the increase of population and growth of solid waste. 15 Ulu Village is one of villages in Jakabaring area that has solid waste problem. Lack waste treatment infrastructure in the Village was made people using the vacant land as a garbage dump. The purpose of this research is to examine the waste treatment infrastructure in 15 Ulu Village. This research data were obtained from the questionnaire and interview local residents, and the data from related institutions. Analysis of the data were using exponential methods for population projection. The result of Â analysis, in 2018 the population of 15 Ulu Village projected as 31.500 people with the volume of solid waste by 94,50 m3/day. Need for temporary landfills shaped container totaling 16 units with a capacity of 6 m3, collection tool the form of motor wagon 20 units with a capacity of 2 m3, and waste carrier vehicles the form of dump trucks totaling 7 units with a capacity of 6 m3. Planned collection patterns with Pattern Individual Indirect Collection, while the transport patterns using the Stationary Container System. Keywords: waste treatment infrastructure, Stationary Container System, volume of solid waste, temporary landfills